(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
Pesticides are chemicals widely used in modern agriculture, and their long-term effects on human health during pregnancy and lactation pose a serious threat. They accumulate in the body and exert a harmful effect on the genotoxic, endocrine systems, leading to oxidative stress. Organophosphorus, organochlorine, carbamate, and pyrethroid pesticides negatively affect DNA synthesis, cell division, gene expression, and epigenetic processes. In particular, the passage of pesticides through the placenta to the fetus, which intensifies oxidative stress and disrupts the activity of cytochrome P450 enzymes, hinders embryonic development. In response, to reduce the risk of pesticides, there is a need to control them, protect pregnant women, and strengthen toxicological monitoring. At the same time, expanding the use of environmentally safe, low-toxicity, or biological pesticides is an important strategy. This approach is crucial for protecting human health and maintaining environmental sustainability.